Atomic-level quantification of twinning shears in magnesium alloy. (1st March 2023) - Li, Quan; Gong, Mingyu; Jiang, Jiancheng; Chen, Yiwen; Ma, Houyu; Wu, Yujuan; Hu, Yongxiang; Liu, Yue; Liu, Guisen; Wang, Jian; Zeng, Xiaoqin
Abstract: Unlike dislocation slips with lattice translation vectors, the shear vector of twinning dislocation or disconnection (TD) is a non-lattice translation vector. Corresponding to the crystallography of twinning, geometrical analysis such as topological model has been widely adopted to define possible TDs that have both step and dislocation character. More importantly, multiple TDs can be defined to achieve the same crystal reorientation but generate different twinning shears. Thus, an accurate measurement of twinning shear allows us to define the character of elementary TD. Here, we quantitatively measured twinning shear of three twinning modes at an atomic level through tracing the twinning induced shear in nanoscale lamellar precipitates under laser shock peening and correspondingly determined the character of elementary TD. According to the measured angle for characteristic planes of nanoscale lamellar precipitates before and after twinning, we determined the twinning shear of 0.617 for { 11 2 ¯ 1 } twinning, which corresponds to a 1/2-layer TD with the Burgers vector of 0 . 024 < 1 ¯ 1 ¯ 26 > as identified in the topological model. Using the same method, a twinning shear of 0.129 is determined for { 10 1 ¯ 2 } twinning, which corresponds to a two-layer TD with the Burgers vector of 0 . 080 < 1 ¯ 011 > . More importantly, this result rules out the so-called pure-shuffle mechanism for { 10 1 ¯ 2 } twinning. A twinning shear of 0.136 is determined for { 10 1 ¯ 1 } twinning, which corresponds to a four-layer TD (or a reassembly of two-layer TDs) with the Burgers vector of 0 . 113 < 10 1 ¯ 2 ¯ > as identified in topological model. These findings may obviate the dissent of twinning mechanisms, and provide an effective method to determine other complex shear mechanisms at an atomic level. Graphical abstract: Image, graphical abstract